New Trends of Islamic Resurgence in Contemporary Malaysia: Sufi-Revivalism, Messianism, and Economic Activism - Hamid, A. Fauzi A. (Studia Islamika, 1999)
This paper, based on research entitled  "Islamic Resurgence in the Periphery: A Study of Political Islam  in Contemporary Malaysia with Special Reference  to the Darul Arqam Movement 1968-1996" (University of Newcastle upon Tyne,  1998), draws upon the systematic, full-blown  government repression of Darul Arqam, a sufi revivalist movement, in 1994. The "Darul Arqam challenge"  casts a significant  light on the various  tactics, methods and strategies  pursued  by Islamic movements in their  route  to power. This paper recognizes  that an analysis of the "Darul Arqam  challenge" is incomplete without a consideration  of long-term  structural  processes putting the 1994 events within a broader historical and ideological perspective. Of particular importance is the gradual concoction of a specific organizational and sociopolitical doctrine, concomitant with the execution of a dynamic economic  enterprise. It is argued that the elegant combination between theory and practice, in implementing Islam in as comprehensive  a manner as possible, serves as the main distinction between Darul Arqam and other contemporary Islamic movements not only in Malaysia but also throughout the ummah.DOI: 10.15408/sdi.v6i3.722